2003
DOI: 10.1124/jpet.102.048355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Ethanol Feeding on Clonidine-Evoked Reductions in Blood Pressure, Heart Rate, and Their Variability: Time-Domain Analyses

Abstract: The effects of chronic ethanol administration on the acute hemodynamic effects of clonidine were investigated in conscious radiotelemetered spontaneously hypertensive rats (SHRs). Changes evoked by clonidine (30 g/kg i.p.) in blood pressure, heart rate, and their variability were evaluated in ethanol [2.5 or 5% (w/v), 12 weeks] and pair-fed control rats. The blood pressure variability was determined as the standard deviation of the mean arterial pressure (SDMAP). Two heart rate variability indices were used, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…In effect, the rMSSD differences between cyclosporine-treated rats and their control counterparts were virtually abolished after atropine administration. Notably, the rMSSD is believed to primarily reflect the vagal activity of the heart [3,31], a view which is supported by the present finding that rMSSD of control rats was reduced after vagal blockade but it was insensitive to β-adrenergic blockade. Together, the present findings implicate alterations in vagal cardiomotor activity, at least partly, in the deleterious effect of cyclosporine on heart rate variability.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In effect, the rMSSD differences between cyclosporine-treated rats and their control counterparts were virtually abolished after atropine administration. Notably, the rMSSD is believed to primarily reflect the vagal activity of the heart [3,31], a view which is supported by the present finding that rMSSD of control rats was reduced after vagal blockade but it was insensitive to β-adrenergic blockade. Together, the present findings implicate alterations in vagal cardiomotor activity, at least partly, in the deleterious effect of cyclosporine on heart rate variability.…”
Section: Discussionsupporting
confidence: 79%
“…The time-domain measurement of hemodynamic variability was employed in the present study to determine changes in the cardiovascular autonomic balance. Time-domain indices correlate with frequency-domain measurements and, therefore, provide a reliable evaluation of cardiovascular autonomic control [3,6,31,32]. The results showed that cyclosporine had no effect on blood pressure or its variability but caused remarkable increases in heart rate and decreases in heart rate variability.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations